Tower Grove Park of the City of St. Louis, Rules and Regulations, 117, § 4 (1883) - (:unkn) unknown (General Publisher, 1883)
All persons are forbidden . . . 4. To carry firearms or to throw stones or other missiles within it.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES